Last chance to see - Adams, Douglas, 1952-2001.; Carwardine, Mark.; MultiMedia Corporation; Voyager Company (Santa Monica, Calif. : Voyager, 1992)
An interactive multimedia exploration of the authors' trip around the world in search of endangered species. Contains the unabridged text of the book Last chance to see, a reading of the entire book by Douglas Adams, and over 800 full-screen color photographs. Allows the user to either read or listen to the book, to choose any chapter within the book, and to explore the many sidebars that provide scientific information about the animals and stories about the authors' experiences as they traveled around the world.
Title from disc container.
Based on the book of the same title which was originally published in 1990.
System requirements: Macintosh LC, LC II, Classic II, SE/30, PowerBook 140 and 170, Quadra 700 and 900, and the II series; 1.5 MB RAM (b/w) or 2 MB RAM (256 colors) or 3 MB RAM (higher color systems); System 6.0.7 or higher; QuickTime (included); hard drive; Macintosh-compatible CD-ROM drive; color monitor for QuickTime; headphones or speakers (optional).
Keywords: Endangered species -- Interactive multimedia